TGF-β signaling in liver and gastrointestinal cancers. Issue 2 (1st September 2016) - Katz, L.H.; Likhter, M.; Jogunoori, W.; Belkin, M.; Ohshiro, K.; Mishra, L.
Highlights: TGF-β plays a prominent driving, context-dependent role in liver and gastrointestinal cancers. TGF-β pathway members have a broad range of functions (profibrotic, immunomodulatory, tumor supressor, and tumor promoter). Mouse models, human genomics and functional studies have provided key insights into this pathway. This review focuses on identifying novel strategies targeting this key pathway to improve outcomes for these lethal cancers. Abstract: Transforming Growth Factor-β (TGF-β) plays crucial and complex roles in liver and gastrointestinal cancers. These include a multitude of distinct functions, such as maintaining stem cell homeostasis, promoting fibrosis, immune modulating, as a tumor suppressor and paradoxically, as a tumor progressor. However, key mechanisms for the switches responsible for these distinct actions are poorly understood, and remain a challenge. The Cancer Genome Atlas (TCGA) analyses and genetically engineered mouse models now provide an integrated approach to dissect these multifaceted and context-dependent driving roles of the TGF-β pathway. In this review, we will discuss the molecular mechanisms of TGF-β signaling, focusing on colorectal, gastric, pancreatic, and liver cancers. Novel drugs targeting the TGF-β pathway have been developed over the last decade, and some have been proven effective in clinical trials. A better understanding of the TGF-β pathway may improve our ability to target it, thus providing more tools to the armamentarium against these deadly cancers.